Psycho-corrective humanity actualization resources for students: sport and arts - Костикова, Ольга; Корсун, Светлана; Шапошникова, Ирина; Суворова, Яна (Slobozhanskyi Herald of Science and Sport, 2017)
Olha Kostikova, Svitlana Korsun, Iryna Shaposhnykova & Yana Suvorova Purpose: to substantiate the perspective effectiveness of the interdisciplinary system "sport – psychoanalysis – art" for effective psychological and pedagogical influence in the development of humanity in students in the teaching and educational process. Material & Methods: observation in higher educational institutions of the pedagogical and sports orientation, theoretical analysis and synthesis of philosophical-psychological and valeo-pedagogical publications on the research problem. Results: considered humanistic significance of sports activities and the arts at the planetary level of human development. The psychoanalytical and philosophical aspects of surrealism are presented in the context of the actualization of humanity in student: future teachers and trainers. Conclusion: theoretically designated psycho-correctional resources in the spectrum of physical, aesthetic and moral education for the progressive dynamics of humanity in the personal development of students.